Nanochannel-confined graphene quantum dots for ultrasensitive electrochemical analysis of complex samples - Lu, Lili (2020)
Herein, we present an electrochemical sensing platform based on nanochannel-confined graphene quantum dots (GQDs) that is able to detect a spectrum of small analytes in complex samples with high sensitivity. Vertically ordered mesoporous silica-nanochannel film (VMSF) is decorated on the supporting electrode, conferring the electrode with excellent antifouling and anti-interference properties through steric exclusion and electrostatic repulsion. The synthesized GQDs with different functionalities are confined in the nanochannels of VMSF through electrophoresis, serving as the recognition element and signal amplifier. Without the usual need of tedious pretreatment, ultrasensitive and fast detection of Hg2+, Cu2+, and Cd2+ (with limits of detection (LOD) of 9.8 pM, 8.3 pM, and 4.3 nM, respectively) and dopamine (LOD of 120 nM) in complex food (Hg2+-contaminated seafood), environmental (soil-leaching solution), and biological (serum) samples are realized as proof-of-concept demonstrations.